ANALISIS PERBANDINGAN DESAIN MOTOR INDUKSI 12 KW DENGAN MEMVARIASI JUMLAH SLOT PADA ROTOR - Andrea Pangestaka Saat; Ilham Aldiansyah; Deni Muswara (JuTEkS (Jurnal Teknik Elektro dan Sains), 2024)
– The industry and transportation technology that continues to growing every year. The electric motor driven drive reduces the use of fossil fuels. Induction motors receive special attention in the general public because of their superior efficiency and compatibility compared to other types of motors, such as low cost, flexibility, easy to control. However, designers face difficulties in designing Induction Motors with high torque, power factor, efficiency and varying number of slots and rotors with special performance, high efficiency and better operational features. This study proposes choice of design type Induction Motors. The design process and analysis program use the Simcenter Motorsolve application. Design model for Induction Motor with output power 12 Kw 50 Hz. The design process focuses on the best analysis of the torque, efficiency, output power, and power factor of the induction motor, with a value of stator slot 24, rotor slot 24, 36, 48 in Simcenter Motorsolve. The performance of the designed motor is analyzed in conditions that are not good, good and very good. The results obtained using the Simcenter Motorsolve application show that the resulting design is accurate and effective.